2013
DOI: 10.4028/www.scientific.net/amm.409-410.1122
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Roundabout Inscribed Circle Diameter to the Traffic Safety

Abstract: The article presents an interesting result of research aimed on traffic safety of roundabouts. The relationship between the inscribed circle diameter of roundabout and the crash rate in the roundabout is presented. There is a certain optimal size of roundabout inscribed circle diameter identified for safe operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The geometric features that affect the safety and capacity of roundabouts include the entry lane width, the number of entry lanes, the rate of deflection for the entry and exit legs, the circulating lane width, the radius of the central island, the flare length, and the radius of the inscribed circle. Mahdalova et al (2013) claim that drivers will traverse the entry curves of roundabouts at a lower speed if all of the geometric features are well designed. The geometric elements of roundabouts are illustrated in Figure 2-4.…”
Section: Design Elements Of Roundaboutsmentioning
confidence: 99%
See 3 more Smart Citations
“…The geometric features that affect the safety and capacity of roundabouts include the entry lane width, the number of entry lanes, the rate of deflection for the entry and exit legs, the circulating lane width, the radius of the central island, the flare length, and the radius of the inscribed circle. Mahdalova et al (2013) claim that drivers will traverse the entry curves of roundabouts at a lower speed if all of the geometric features are well designed. The geometric elements of roundabouts are illustrated in Figure 2-4.…”
Section: Design Elements Of Roundaboutsmentioning
confidence: 99%
“…Table 2.2 shows common design vehicles considered for roundabouts and their corresponding required inscribed circle diameter. Mahdalova et al (2013) evaluated the effect of the inscribed circle radius on the safety of roundabouts. The results of their analysis revealed that increases in the radius of the inscribed circle reduce the rate of collisions.…”
Section: Size Of Roundaboutsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past 20 years, scholars have conducted relatively in-depth and thorough studies on roundabouts in terms of traffic safety and efficiency using different approaches. Mahdalova et al [25] presented the relationship between the inscribed circle diameter of a roundabout and the crash rate. Furthermore, Kim and Choi [26] developed a model to investigate the relationship between crashes and roundabout geometric characteristics to reveal major geometric elements of roundabout safety.…”
Section: Literature Reviewmentioning
confidence: 99%